The performance of Africa's international courts : using litigation for political, legal, and social change - Gathii, James Thuo (Oxford : Oxford University Press, 2021)
This text argues that we must look beyond the traditional criteria of compliance and effectiveness to judge the performance of Africa's international courts. It demonstrates how these courts are important venues for activists and opposition parties to wage political, social, environmental, and legal struggles on the international stage.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 6, 2021).
Keywords: International courts -- Africa